2022
DOI: 10.3390/ijerph192416728
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity and Incorrect Body Posture: Impact on Physical Activity and the Therapeutic Role of Exercise

Abstract: Obesity is associated with various dysfunctions of the organism, including musculoskeletal problems. In this narrative review, we aim to consider postural problems in children and adolescents with obesity, focusing on the relationship with its negative impact on physical activity, and to discuss the role of exercise as a therapeutic approach. The body reacts to excess weight by changing its normal balance, and the somatosensory system of children with obesity is forced to make major adjustments to compensate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 108 publications
(212 reference statements)
0
6
0
1
Order By: Relevance
“…Motor competence (MC) is a general expression that describes several terms used in the literature (i.e., motor proficiency, motor performance, fundamental movement/motor skills, motor ability, and motor coordination) to evaluate goal-directed human movement [ 1 , 2 , 3 , 4 ]. Motor development in children integrates both fine and gross motor coordination abilities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Motor competence (MC) is a general expression that describes several terms used in the literature (i.e., motor proficiency, motor performance, fundamental movement/motor skills, motor ability, and motor coordination) to evaluate goal-directed human movement [ 1 , 2 , 3 , 4 ]. Motor development in children integrates both fine and gross motor coordination abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have shown the existence of strong links between motor competence and PA, highlighting the importance of the latter in maintaining a healthy weight alongside supporting correct motor development in children [ 2 , 3 ]. The World Health Organization (WHO) always underlines that PA and active lifestyle promotion should be prioritized to prevent health diseases since exercise is proven to improve cardiovascular fitness and modulate inflammatory processes in all populations [ 4 ]. However, the higher levels of sedentary behavior among children and adolescences reported in the recent literature have led to a higher risk of weight gain, which is reflected in the steep increase in obesity prevalence and incidence in youth [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…O excesso de massa corporal assim como o baixo nível de atividade física podem ter um grande impacto nos parâmetros posturais em crianças e adolescentes (3). De acordo com a Organização Mundial de Saúde (OMS), a obesidade é definida como o acúmulo excessivo de gordura corporal, capaz de acarretar prejuízos importantes à saúde (4).…”
Section: Introductionunclassified